The Effect Of Human Resource Quality And Work Professionalism On Employee Performance: Study On University Educational Personnel 17 August 1945 Semarang - Muhammad Adnan Wazan; Suparmi Suparmi; Galuh Juniarto (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
This research aims to determine the influence of the quality of Human Resources and work professionalism on the performance of educational staff at the University of 17 August 1945 Semarang. The population used was all educational staff (tendik) at the University of 17 August 1945 Semarang with a total of 140 people, the sample size used was 104 respondents, with a sampling technique using proportionate random sampling. The data source used is primary data, with data collection methods using questionnaires. The data analysis technique used is multiple linear regression analysis. The results of the hypothesis test showed that the quality of human resources had a positive and significant effect on employee performance, and work professionalism had a positive and significant effect on employee performance. The coefficient of determination value is 0.463, meaning that the quality of Human Resources and work professionalism can explain variations in employee performance variables by 46.3 percent, so it still needs to be followed up with further research, especially related to individual aspects and employee performance